Caracterização e avaliação da atividade fotocatalítica de catalisadores baseados no TiO2, sintetizados mediante hidrólise em uma mistura de solventes - Machado, Werick Alves (2016)
This study involved the synthesis of photocatalysts based on titanium dioxide (TiO2). The photocatalysts were synthesized by the sol-gel method using three different proportions of acetone (25%, 50% and 75% v/v) in water/acetone mixtures, in order to control the hydrolysis of the precursor of titanium (titanium tetraisopropoxide). Aiming to investigate the structural, morphological and electronic changes provoked by the use of the solvent mixtures, different methodologies were used to characterize the oxides, such as X-ray diffraction (XRD), RAMAN spectroscopy, UV-Vis diffuse reflectance spectroscopy, and measurements of specific surface area (BET). XRD combined to RAMAN analyses revealed that the products are two-phase highly crystalline oxides involving anatase as main phase and brookite. Besides, the refined XRD using the method of Rietveld demonstrated that the presence of acetone during the synthesis influenced in the composition of the crystalline phases, increasing the proportion of the brookite phase between 13 and 22%. The band gap energy of these oxides practically did not suffer changes as function of the synthesis conditions. As shown by the isotherm, these photocatalysts are mesoporous materials with mean diameter of pores of 7 nm and approximately 20% of porosity. The surface area of the oxides prepared by hydrolysis in presence of acetone was 12% higher compared to the bare oxide. After characterized, these oxides had their photocatalytic activities evaluated by photodegradation of the azo dyes Ponceau 4R (P4R), Tartrazine (TTZ) and Reactive Red 120 (RR120), and also by the ability to mediate the photocatalytic production of hydrogen. Using the most efficient photocatalyst, the mineralization achieved for the dyes P4R, RR120 and TTZ was of respectively 83%, 79% and 56% in 120 minutes of reaction, while the discoloration of P4R e RR120 reached 100% and 94% for TTZ. In addition, the same photocatalyst in the presence of 0.5% w/w of Platinum and suspended in a 5:1 v/v water/methanol mixture, produced 56 mmol of gaseous hydrogen in five hours of experiment, corresponding to a specific rate of hydrogen production of 139.5 mmol h-1 g-1.